2019
DOI: 10.1146/annurev-food-032818-121401
|View full text |Cite
|
Sign up to set email alerts
|

Source, Extraction, Characterization, and Applications of Novel Antioxidants from Seaweed

Abstract: Driven by a general demand for clean labels on food and cosmetic products, these industries are currently searching for efficient natural antioxidants to replace synthetic antioxidants. Seaweed contains several compounds with antioxidative properties (phlorotannins, pigments, tocopherols, and polysaccharides). It is possible to extract these compounds via different extraction techniques, which are discussed in this review. Among the abovementioned compounds, phlorotannins are probably the most important in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 132 publications
(133 reference statements)
2
119
0
Order By: Relevance
“…Seaweeds have antioxidant properties due to the presence of phenols, carotenoid fucoxanthin, tannins and phlorotannins, polysaccharides (fucoidans and laminarans in brown seaweeds; ulvans in green seaweeds and carrageenans, porphyrin and agar in red seaweeds) [113]. The highest concentrations of phenols and phlorotannins have been observed in brown seaweed, up to 12-14% DM in Ascophhyllum nodosum, Fucus spp.…”
Section: Influence On Antioxidant Functionmentioning
confidence: 99%
“…Seaweeds have antioxidant properties due to the presence of phenols, carotenoid fucoxanthin, tannins and phlorotannins, polysaccharides (fucoidans and laminarans in brown seaweeds; ulvans in green seaweeds and carrageenans, porphyrin and agar in red seaweeds) [113]. The highest concentrations of phenols and phlorotannins have been observed in brown seaweed, up to 12-14% DM in Ascophhyllum nodosum, Fucus spp.…”
Section: Influence On Antioxidant Functionmentioning
confidence: 99%
“…Particularly, numerous brown seaweed crude extracts (acetonic, aqueous, methanolic, and ethanolic) have shown to possess antioxidant [15,16] and antidiabetic (e.g., α-amylase and α-glucosidase inhibition) activities [14,[17][18][19]. ese activities are related to the presence of phenolic compounds, phlorotannins, pigments, tocopherols, polysaccharides, fatty acids, and peptides in the seaweed extracts [15,[20][21][22][23][24][25][26][27][28]. e main compounds reported as potent α-amylase and α-glucosidase inhibitors are as follows: phloroglucinol derivatives such as dieckol, 8,8′-bieckol, phlorofucofuroeckol, fucophloroethol, and phlorotannins with low PGU [23,25,[29][30][31], fucoidan [3,32,33], and oleic, linoleic, and eicosapentaenoic acids [24].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the major compounds contributing to overall antioxidant activity in seaweed are phenolic compounds and polysaccharides, the latter alone or associated with other components such as polyphenols, amino acid, protein, lipids, and nucleic acids residues, and sometimes polysaccharide conjugates [28,34]. Hence, TPC and polysaccharides, in combination with in vitro antioxidant assays, are typically used to screen for seaweed antioxidant activity [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Walsh, et al (398) reported osteogenic potential of brown seaweeds Laminaria digitata and Ascophyllum nodosum. Seaweed contains several compounds with antioxidant properties (phlorotannins, pigments, tocopherols, flavonoids, polyphenols and polysaccharides) [399]. Antioxidant properties of Fucus vesiculosus and Ascophyllum nodosum (due to phlorotannins) [399], Turbinaria conoides (2H-pyranoids) [400], Ulva clathrate (phenolics and flavonoid contents) [401], Bifurcaria bifurcate ( Figure 21) (diterpenes eleganolone and eleganonal) [402], Cystoseira spp.…”
Section: Other Health Issuesmentioning
confidence: 99%